Inovasi Terhadap Pendidikan Agama Islam Berbasis Multikultural Dalam Al Qur'an Dan Hadist - Hidayaturrahman, Muhammad (DAWUH : Islamic Communication Journal, 2022)
Abstract Multicultural-based Islamic religious education in the Qur'an and Hadith is a topic that is widely discussed. This paper examines what innovations can be made to teach and rectify hoaxes about multicultural-based Islamic religious education in the Koran and Hadith. This research is a type of library research. The conclusion of this paper is that there are several innovations that can be made to teach multicultural-based Islamic religious education in the Quran and Hadith by utilizing information technology in the world of education, making many podcasts, developing social media content. This can be a means of information resources to introduce and straighten out hoaxes related to multicultural-based Islamic religious education in the Al Quran and Hadith.. Abstrak Pendidikan agama islam berbasis multikultural dalam Al Quran dan Hadist menjadi sebuah topic yang ramai diperbincangkan. Tulisan ini mengkaji apa saja inovasi yang dapat dilakukan untuk mengajarkan dan meluruskan hoax mengenai Pendidikan agama islam berbasis multikultural dalam Al Quran dan Hadist. Penelitian ini berjenis penelitian kepustakaan. Kesimpulan tulisan ini adalah ada beberapa inovasi yang dapat dilakukan untuk mengajarkan mengenai pendidikan agama islam berbasis multikultural dalam Al Quran dan Hadist dengan memanfaatkan teknologi informasi dalam dunia pendidikan, membuat banyak podcast, mengembangkan konten media sosial. Ini bisa jadi sarana sumber informasi untuk mengenalkan serta meluruskan hoax yang berkaitan dengan pendidikan agama islam berbasis multikultural dalam Al Quran dan Hadist..